2022
DOI: 10.1002/pros.24459
|View full text |Cite
|
Sign up to set email alerts
|

Presence of cells in the polyaneuploid cancer cell (PACC) state predicts the risk of recurrence in prostate cancer

Abstract: Background:The nonproliferating polyaneuploid cancer cell (PACC) state is associated with therapeutic resistance in cancer. A subset of cancer cells enters the PACC state by polyploidization and acts as cancer stem cells by undergoing depolyploidization and repopulating the tumor cell population after the therapeutic stress is relieved. Our aim was to systematically assess the presence and importance of this entity in men who underwent radical prostatectomy with curative intent to treat their presumed localize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Presence of cells in the PACC state within primary tumors is generally associated with poorer prognosis [ 55 , 56 ]. Recently, it was shown that the presence of PACC state cells in the primary tumors of men with prostate cancer who underwent radical prostatectomy with curative intent is predictive of lower metastasis-free survival [ 57 , 58 ]. Additionally, rapid autopsy of 5 men with metastatic prostate cancer revealed presence of cells in the PACC state in all distant metastatic lesions analyzed [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presence of cells in the PACC state within primary tumors is generally associated with poorer prognosis [ 55 , 56 ]. Recently, it was shown that the presence of PACC state cells in the primary tumors of men with prostate cancer who underwent radical prostatectomy with curative intent is predictive of lower metastasis-free survival [ 57 , 58 ]. Additionally, rapid autopsy of 5 men with metastatic prostate cancer revealed presence of cells in the PACC state in all distant metastatic lesions analyzed [ 59 ].…”
Section: Introductionmentioning
confidence: 99%
“…L-DOXR cells exhibit increased genomic content (4N+) as compared to WT cells. The presence of cells with increased nuclear size and increased genomic content has been demonstrated to be associated with poor clinical outcomes in several types of cancers ( Alharbi et al, 2018 ; Amend et al, 2019 ; Fei et al, 2015 ; Imai et al, 1999 ; Liu et al, 2018 ; Lv et al, 2014 ; Mukherjee et al, 2022 ; O’Connor et al, 2002 ; Saini et al, 2022 ; Trabzonlu et al, 2023 ). We analyzed the occurrence of cells with increased nuclear size in human TNBC patients.…”
Section: Resultsmentioning
confidence: 99%
“…This characteristic of PGCC has been reported in vitro in primary cultures of ovarian cancer [ 6 ] and in cell lines derived from leukemic cells [ 27 ]. It is thought to be involved in the origin of PGCC-derived proliferating tumor cells in patients with cancer recurrence [ 9 , 28 , 29 ]. Although it is difficult to definitively demonstrate PGCC budding by images of cells detected in biological liquids from patients, published studies clearly indicate this possibility [ 27 , 28 , 30 ].…”
Section: Discussionmentioning
confidence: 99%